Removal Of Methylene Blue Dye Using Palm Trunk Based Activated Carbon Via Microwave Irradiated: Optimization, Isotherm, Kinetic And Thermodynamic Studies - Mohamad Hafiz Baharudin; Mohamad Firdaus Mohamad Yusop; Muhammad Nasri Nasehir Khan; Muhammad Azan Tamar Jaya; Mohd Azmier Ahmad (Universiti Putra Malaysia, 2024)
Indexed by Scopus